Genetic resources of Stylosanthes species - Hanson, Jean; Heering, J.H. (International Livestock Centre for Africa, 1994)
The genus Stylosanthes contains about 30 species of which most are native to South and Central America, except for S. erecta and S. fruticosa which are native to Africa. The seven major species that have been used as livestock feed have been widely collected and their germplasm stored in genebanks. Currently ILCA, CIAT and CSIRO hold about 4000 distinct accessions of Stylosanthes species in their genebanks. The available germplasm shows considerable variability in adaptation to agro-ecological zones and soil pH. This germplasm is available free of charge for use in forage research and development programmes, but only about 25 percent has been screened for adaptability as an animal feed in West Africa. Several accessions have been identified as promising and have been incorporated into fodder banks for protein supplementation of livestock feeds. There is considerable potential for further selection and use of this valuable germplasm as part of sustainable crop-livestock systems in sub-Saharan Africa.